Pembuatan Video Animasi Gerakan Sholat Materi Fiqih Berdasarkan 4 Mazhab di Madrasah Tsanawiah - Nurhasanah, Enung; Asmedy, Asmedy; Idhar, Idhar; Alfisyah, Nur Fania; Ferdianto, Ferdianto (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Assistance in making animated videos of prayer movements with Fiqh material based on the four schools of thought for Fiqh teachers at MTsN 1 Dompu aims to increase teacher competence in creating animated video-based learning media and support the implementation of the Independent Curriculum with digital technology. The mentoring method consists of three stages: preparation, implementation, and evaluation. Preparation includes a needs survey and program outreach. Implementation includes training on Fiqh material based on four schools of thought and making animated videos with Canva. The evaluation assesses the increase in teacher competence in using technology and creating interactive learning media. The evaluation results show a significant increase in the competence of Fiqh teachers at MTsN 1 Dompu. As many as 90% of participants experienced marked progress in understanding Fiqh material related to prayer movements based on the four schools of thought and in skills in using digital technology. Teachers are not only able to master the basic concepts of making animated videos, but also apply them independently in creating interactive and interesting animation-based learning media. Previously, most teachers relied on conventional methods, but after participating in the training, they showed increased ability to design visual content that supports learning. Apart from that, the evaluation results also noted that teachers felt more confident in implementing the Independent Curriculum through a creative approach, which is expected to increase student interest and involvement in the teaching and learning process. This success reflects the effectiveness of the training and its potential for sustainability in the future, where teachers are ready to develop more innovative learning media. In conclusion, this activity succeeded in increasing teacher readiness in implementing the Independent Curriculum through interactive and innovative learning media, which has the potential to make learning more effective and interesting for students.